2022
DOI: 10.1038/s41398-022-02069-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of activity-induced Egr3-dependent genes reveals genes associated with DNA damage response and schizophrenia

Abstract: Bioinformatics and network studies have identified the immediate early gene transcription factor early growth response 3 (EGR3) as a master regulator of genes differentially expressed in the brains of patients with neuropsychiatric illnesses ranging from schizophrenia and bipolar disorder to Alzheimer’s disease. However, few studies have identified and validated Egr3-dependent genes in the mammalian brain. We have previously shown that Egr3 is required for stress-responsive behavior, memory, and hippocampal lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…3, B and C ) ( 49 , 50 ). Our observations that nr4a2b and spp1 are down-regulated in egr3 mutants agree with published reports in mammals showing that EGR3 is upstream of Nr4a2 ( 51 ) and that NR4A2 activates SPP1 expression by binding to its promoter ( 52 ). Moreover, EGR3 ( 53 , 54 ), NR4A2 ( 55 ), and SPP1 ( 56 , 57 ) promote endothelial cell migration downstream of vascular endothelial growth factor (VEGF), supporting the model that Egr3 is necessary for EdC migration during valvulogenesis.…”
Section: Resultssupporting
confidence: 93%
“…3, B and C ) ( 49 , 50 ). Our observations that nr4a2b and spp1 are down-regulated in egr3 mutants agree with published reports in mammals showing that EGR3 is upstream of Nr4a2 ( 51 ) and that NR4A2 activates SPP1 expression by binding to its promoter ( 52 ). Moreover, EGR3 ( 53 , 54 ), NR4A2 ( 55 ), and SPP1 ( 56 , 57 ) promote endothelial cell migration downstream of vascular endothelial growth factor (VEGF), supporting the model that Egr3 is necessary for EdC migration during valvulogenesis.…”
Section: Resultssupporting
confidence: 93%
“…To check to what extent the candidate transcription factor genes are actively transcribed in the cell types where the de novo motifs are accessible, we examined their RNA expression levels using public scRNA-seq data of the adult mouse cortex 13 and gene activity levels using scATAC-seq data 33 (see “Methods”). We confirmed that specific transcription factors of the candidates that regulate neural differentiation and/or neuronal activity are highly expressed in each cell population 7 , 8 , 37 40 (Fig. 2 d, Supplementary Fig.…”
Section: Resultssupporting
confidence: 74%
“…In the present study, we uncover a novel C1ql2-dependent regulatory pathway through which Bcl11b controls the structural as well as functional integrity of hippocampal MFS in adult mice. We show that SV recruitment to the AZ of MFS, as well as the expression of MF-LTP, depend on C1ql2, which is a direct functional target of Recent studies suggested Nrxn3, as well as C1ql2, to be associated with neuropsychiatric disorders (Hishimoto et al, 2007;Hu et al, 2013;Huggett & Stallings, 2020a, 2020bMarballi et al, 2022). Our study for the first time identifies a Bcl11b/C1ql2/Nrxn3-dependent signaling pathway in the control of basic structural and functional properties of MFS.…”
Section: Discussionmentioning
confidence: 55%
“…Finally, we show that C1ql2 controls SV recruitment through a direct interaction with presynaptic Nrxn3(25b+), while LTP depends on C1ql2 signals independent of Nrxn3 interaction. Recent studies suggested Nrxn3, as well as C1ql2, to be associated with neuropsychiatric disorders (Hishimoto et al, 2007; Hu et al, 2013; Huggett & Stallings, 2020a, 2020b; Marballi et al, 2022). Our study for the first time identifies a Bcl11b/C1ql2/Nrxn3-dependent signaling pathway in the control of basic structural and functional properties of MFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation